THE RELATIONSHIP BETWEEN QUALITY OF THE JAMSOSTEK MOBILE TO CONSUMER SATISFACTION - Ahmad Wardani, Sony (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of this study was to determine the relationship between the quality of the Jamsostek Mobile Application and customer satisfaction. Respondents on this study were company participants that registered to BPJS Ketenagakerjaan through the Jamsostek Mobile application. The data collection technique used in this study was a survey, by distributing questionnaires to get 155 respondents. The results of this study indicate that the use of the Jamsostek Mobile application can impact to customer satisfaction, meaning that Jamsostek Mobile has increased customer satisfaction.